Oral supplementation with a nutraceutical formulation containing omega-3 fatty acids, vitamins, minerals, and antioxidants in a large series of patients with dry eye symptoms: results of a prospective study - Gatell-Tortajada J (Dove Medical Press, 2016)
Jordi Gatell-TortajadaOn behalf of the Large Dry Eye Clinical Study Group (LDECSG)Cornea and Ocular Surface Department, Institut Català de Retina, Barcelona, SpainPurpose: To assess the benefits and tolerability of a dietary supplement based on omega-3 fatty acids to relieve dry eye symptoms.Methods: A total of 1,419 patients (74.3% women, mean age 58.9 years) with dry eye syndrome using artificial tears participated in a 12-week prospective study. Patients were instructed to take 3 capsules/day of the nutraceutical formulation (Brudysec® 1.5 g). Study variables were dry eye symptoms (scratchy and stinging sensation, eye redness, grittiness, painful and tired eyes, grating sensation, and blurry vision), conjunctival hyperemia, tear breakup time (TBUT), Schrimer I test, and Oxford grading scheme.Results: At 12 weeks, each dry eye symptom improved significantly (P<0.001), and the use of artificial tears decreased significantly from 3.77 (standard deviation [SD] =2.08) at baseline to 3.45 (SD =1.72) (P<0.01). In addition, the Schirmer test scores and the TBUT increased significantly, and there was an increase in patients grading 0–I in the Oxford scale and a decrease of those grading IV–V. Significant differences in improvements of dry eye symptoms were also found in compliant versus noncompliant patients as well as in those with moderate/severe versus none/mild conjunctival hyperemia.Conclusion: Oral ω-3 fatty acids supplementation was an effective treatment for dry eye symptoms.Keywords: dry eye symptoms, artificial tears, omega-3 polyunsaturated fatty acids, nutraceutical supplement, ocular inflammation, eye discomfort